PGE2 protects against heart failure through inhibiting TGF-β1 synthesis in cardiomyocytes and crosstalk between TGF-β1 and GRK2. (November 2022) - Fu, Jing; Li, Li; Chen, Long; Su, Congping; Feng, Xiuling; Huang, Kai; Zhang, Laxi; Yang, Xiaoyan; Fu, Qin
Abstract: Inflammation plays a central role in the development of heart failure. Prostaglandin E2 (PGE2) is a key mediator of the inflammatory process in the cardiovascular system. However, the role of PGE2 in heart failure is complex and controversial. A recent report suggested that PGE2 inhibits acute β adrenergic receptor (β-AR) stimulation-enhanced cardiac contractility. The aim of this study was to characterize the influence of PGE2 on chronic β-AR stimulation-induced heart failure. Male C57BL/6 J mice received isoproterenol (ISO) or vehicle for 4 weeks. PGE2 significantly reversed ISO-induced cardiac contractile dysfunction and remodeling. Mechanically, ventricular myocytes were found to be an important source of TGF-β1 in ISO-model and PGE2 ablated TGF-β1 synthesis in cardiomyocytes through inhibition of β-AR activated PKA-CREB signaling. Furthermore, PGE2 significantly suppressed TGF-β1-GRK2 crosstalk-induced pro-hypertrophy and pro-fibrotic signaling in cardiomyocytes and cardiac fibroblasts, respectively. Pharmacological inhibition of GRK2 also attenuated contractile dysfunction and cardiac hypertrophy and fibrosis in ISO-model. These studies elucidate a novel mechanism by which PGE2 reduces TGF-β1 synthesis and its downstream signaling in heart failure and identify PGE2 or TGF-β1-GRK2 crosstalk as plausible therapeutic targets for preventing or treating heart failure induced by chronic β-AR stimulation. Graphical abstract: Unlabelled Image Highlights: Ventricular myocytes are important source of TGF-β1 in chronic Isoproterenol (ISO)-induced heart failure. TGF-β1-GRK2 crosstalk in cardiomyocytes and cardiac fibroblasts promotes cardiac hypertrophy and fibrosis. PGE2 reverses ISO-induced heart failure by inhibiting TGF-β1 secretion from cardiomyocytes. PGE2 reverses ISO-induced heart failure by disrupting TGF-β1-GRK2 crosstalk in cardiomyocytes and cardiac fibroblasts. GRK2 inhibitor paroxetine ameliorates ISO-induced cardiac hypertrophy and fibrosis. GRK2 inhibitor paroxetine ameliorates ISO-induced cardiac hypertrophy and fibrosis.